2020
DOI: 10.1186/s12955-020-01308-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationships between mental disorders, self-reported health outcomes and positive mental health: findings from a national survey

Abstract: Background: The link between mental illness and mental health is gaining focus in research and practice. This study aimed to investigate the association of mental disorders with positive mental health (PMH), overall health and quality of life. In addition, the role of PMH in mediating the relationships between mental disorders and health outcomes was assessed. Methods: The study sample comprised 2270 residents aged 18 years and above who participated in a nationally representative, cross-sectional survey estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Mental health has been defined as both the absence of psychological distress, including symptoms of anxiety, depression, stress, and associated mental disorders, and the presence of positive psychological well-being, which includes factors like life satisfaction, optimism, and positive emotion [ 31 - 33 ]. Research has demonstrated that psychological distress and positive psychological well-being are related, but distinct constructs that uniquely contribute to the prediction of various health outcomes [ 34 , 35 ], including cardiovascular health [ 36 , 37 ], and therefore a complete description of mental health and its relationship with CVD risk should include both.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health has been defined as both the absence of psychological distress, including symptoms of anxiety, depression, stress, and associated mental disorders, and the presence of positive psychological well-being, which includes factors like life satisfaction, optimism, and positive emotion [ 31 - 33 ]. Research has demonstrated that psychological distress and positive psychological well-being are related, but distinct constructs that uniquely contribute to the prediction of various health outcomes [ 34 , 35 ], including cardiovascular health [ 36 , 37 ], and therefore a complete description of mental health and its relationship with CVD risk should include both.…”
Section: Introductionmentioning
confidence: 99%
“…Singapore is a multi-ethnic Southeast Asian country of approximately 4 million residents (citizens and permanent residents) comprising 74.4% Chinese, 13.4% Malays, and 9.0% Indians, and other ethnic groups (3.2%) [ 5 ]. The SF-12v2 has been utilized for research within Singapore amongst different populations and samples: patients with peritoneal dialysis [ 14 , 58 ], arthritis [ 17 ], mental illness [ 51 ], substance and alcohol use disorders [ 26 , 59 ], older adults [ 57 ], and the general population [ 28 , 47 ]. It appears that the usage of the SF-12v2 within Singapore will continue to increase, and hence there is a need to examine its factor structure within the general population.…”
Section: Introductionmentioning
confidence: 99%
“…It was measured using the standard question: "Generally, how do you evaluate your health?" which participants rated using a 6-point scale ranging from 1 ("very bad") to 6 ("excellent") [62].…”
Section: Instruments and Measuresmentioning
confidence: 99%